Shared bicycle study to help reduce carbon emissions in Beijing - S. Sun; B. Wang; A. R. Li (Energy Reports, 2020)
The shared bicycles had become an important choice for Beijing citizens to travel "the last kilometer" on a daily basis. By replacing buses and cars, sharing bicycles can reduce urban carbon emissions, and only occupy a small area of parking space, thus improving urban land use efficiency. A comprehensive field survey was conducted on 45 subway stations and 174 exits of the Metro Line 10. Through the method of mathematical statistics and graph analysis, the change of the number of shared bicycles on the subway line 10 in the middle of the day was studied. At the same time, the needs and characteristics of the user types and actions were analyzed. Based on the characteristics of the surrounding land, this paper studies the rationality and potential of reducing carbon emission by sharing bicycle are studied and provides data support for the government to increase the parking space of shared bicycles.
Keywords: 330; Reduce carbon emissions; Shared bicycle; Subway station